Investigation on characteristics of Monte Carlo model of single electron transistor using Orthodox theory. (December 2021) - Singh, Ngangbam Phalguni; Suman, Shruti; Ramachandran, Thandaiah Prabu; Sharma, Tripti; Raja, Selvakumar; Rangasamy, Rajasekar; Parasuraman, Manikandan; Sengan, Sudhakar
Abstract: An improved Monte Carlo Model of the Single Electron Transistor using the Orthodox Theory and Master Equations is proposed in this paper. The modifications are done in the parasitic parameters to investigate the current–voltage characteristics of a Single Electron Transistor. This work is carried out for determining the parasitic parameters and their impacts on the characteristics of the Single Electron Transistor. The simulation results show that the Coulomb stair-case is highly visible at the gate capacitance of C g = 0.2 x 10 - 18 F with the highest conductance peak of 7.3 x 10 - 8 S i e m e n s ( S ) . The consecutive conductance peaks are separated by a regular interval, i.e., voltage bias. This determines the Coulomb Blockade in Quantum Dot Island and tunneling of the electron in a controlled manner. The bias voltage is 0.4 V and charging, or electrostatic energy is 0.190725 e V .